Analytic study to the physical element ( power and flexibility) in a sport session according to the timing horror in the modern strategic learning - Boumezrag , Cheikh; رواب عمار (sports creativity, 2025)
the current study aimed to uncover the contribution of the physical education and sports class in the school environment improve some elements of physical fitness (strength and flexibility) for intermediate stage pupils(12-14 years),competency approach. The researcher used hear the descriptive approach, on a sample consisting of professor of physical education and sports in-Tiaret- represented in a questionnaire in a order to draw conclusions and demonstrate the importance of repeating the number of classes of physical education per week and to the achieve the objectives, so that the results concluded in the end that the Increase in the size of the physical education subject contributes to some extent to improving strength and flexibility by repeating the learning process more than once a week, which is in line with what the student needs to gain good physical fitness It helps build a strong and balanced personality.